The principle of game in novels of M. Z. Danielewski and J. S. Foer - Kashkan, Tatsiana A. (Journal of the Belarusian State University. Philology, 2024)
The article examines the phenomenon of game in literature. A detailed analysis of the principle of the game is carried out in the novels of American writers M. Z. Danielewski «House of leaves» and J. S. Foer «Everything is illuminated», «Extremely loud and incredibly close». Literary game can be traced at all levels of the text: plot-compositional, ideological-semantic and linguistic. The analysis reveals the compositional, structural and linguistic features of these texts. The author of the study comes to the conclusion that, along with the narrative strategies of writers, this prose is characterised by techniques of deconstruction through game as a plot-forming principle, game as a principle of synthesis of genre, game with the figures of the author, hero and reader, as well as through language game.